THE USE OF ONTOLOGIES OF EDUCATIONAL PURPOSES FOR THE FORMATION OF EDUCATIONAL AND OPERATIONAL ENVIRONMENT - Буров, О.; Царик, О. (Proceedings of National Aviation University, 2012)
Object of study - an ontology for educational purposes and theirimpact on the effectiveness of training. Purpose -substantiation the feasibility of using ontologies of educational purposes for the formation learningenvironment of specialists in the field of aviation. The method of study - an analysis of existing methods and meansofforming an ontology for educational purposes, in particular by the method of structuring the domain and the methodof generalization. The main aspects of the formation of knowledge bases for educational purposes with the useof ontologies are considered. The approaches and means of forming domains of knowledge bases based on ontologiesare described. Shaped ergonomic requirements for content and form of ontologies for educational purposes. It isestablished that the introduction and use of ontologies for educational purposes requires a much larger audience insearch of independence and mastery of new knowledge that provides a high level of intensification of educationalprocess, as well asincrease the efficiency of the educational process by intensifyingand enhancing learning andcognitive activities, giving her the creative direction of research that is a prerequisite for more effective learning